2009
DOI: 10.5551/jat.2188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obstructive Sleep Apnea with Intermittent Hypoxia on Platelet Aggregability

Abstract: Aim:Obstructive sleep apnea (OSA) is a risk factor for cardiovascular diseases. Platelets play key roles in the development of atherothrombosis. Several studies assessing platelet activation in patients with OSA have been published; however, there have been only a few studies with a small number of patients with OSA investigating platelet aggregability, which evaluates platelet aggregation more directly than the platelet activation status. We aimed to investigate the effects of OSA and nasal continuous positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 33 publications
(31 reference statements)
1
57
0
Order By: Relevance
“…Adenosine diphosphate-induced platelet aggregability increased significantly in patients with moderate-to-severe OSA compared to that in controls; CPAP treatment improves platelet aggregability in these patients. 24 Similar to our results one study found that 6 months of CPAP therapy significantly reduced MPV values in patients with severe OSA. 15 The decreased MPV could be explained by decreased hypoxia and inflammation, as postulated in that study, which could help to decrease the frequency of cardiovascular complications in OSA patients.…”
Section: Discussionsupporting
confidence: 81%
“…Adenosine diphosphate-induced platelet aggregability increased significantly in patients with moderate-to-severe OSA compared to that in controls; CPAP treatment improves platelet aggregability in these patients. 24 Similar to our results one study found that 6 months of CPAP therapy significantly reduced MPV values in patients with severe OSA. 15 The decreased MPV could be explained by decreased hypoxia and inflammation, as postulated in that study, which could help to decrease the frequency of cardiovascular complications in OSA patients.…”
Section: Discussionsupporting
confidence: 81%
“…However, lowering platelet numbers in patients with cancer requires careful titration, as thrombocytopenia can easily lead to life-threatening bleeding complications. Although platelet function and numbers can change under hypoxic conditions (27)(28)(29)55), their role in tumor hypoxia, especially with regard to antiangiogenic therapy-induced hypoxia, is not well understood. We showed that increased platelet infiltration after withdrawal of antiangiogenic therapy was dependent on expression of FAK in platelets.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that platelets enhance tumor growth (19,23,26), chemoresistance (20), and metastasis (21,22). Although platelet number and function can be altered by hypoxia (27)(28)(29), the functional effects of hypoxia in the tumor microenvironment on platelets are unknown. Therefore, we examined whether platelet infiltration into the tumor microenvironment could contribute to tumor growth following cessation of antiangiogenic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…CPAP relieves airway obstruction and reduces hypoxia and inflammation [34]. CPAP treatment decreases platelet aggregability [35]. Several studies demonstrated the increase in blood viscosity before and the decrease after CPAP treatment [36,37].…”
Section: Discussionmentioning
confidence: 99%